2004
DOI: 10.1158/0008-5472.can-04-0504
|View full text |Cite
|
Sign up to set email alerts
|

Src Family Kinases Mediate Epidermal Growth Factor Receptor Ligand Cleavage, Proliferation, and Invasion of Head and Neck Cancer Cells

Abstract: Head and neck squamous cell carcinomas (HNSCCs) are characterized by up-regulation of the epidermal growth factor receptor (EGFR). We previously reported that a gastrin-releasing peptide/gastrin-releasing peptide receptor (GRP/GRPR) autocrine growth pathway is activated early in HNSCC carcinogenesis. GRP can induce rapid phosphorylation of EGFR and p42/44 mitogen-activated protein kinase (MAPK) activation in part via extracellular release of transforming growth factor ␣ (TGF-␣) by matrix metalloproteinases (MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
106
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(111 citation statements)
references
References 42 publications
5
106
0
Order By: Relevance
“…Phosphorylation of TACE may result in its translocation to its targets or the formation of a functional complex of Src and TACE on the membrane. We previously reported that Src family kinases contribute to GRP-induced EGFR phosphorylation in SCCHN (15). Both c-Src and TACE are located in punctuate foci in the cytosol compatible with the association of c-Src and TACE with intracellular membranes through myristoylation of the Src N-terminal domain and TACE transmembrane domain, respectively.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Phosphorylation of TACE may result in its translocation to its targets or the formation of a functional complex of Src and TACE on the membrane. We previously reported that Src family kinases contribute to GRP-induced EGFR phosphorylation in SCCHN (15). Both c-Src and TACE are located in punctuate foci in the cytosol compatible with the association of c-Src and TACE with intracellular membranes through myristoylation of the Src N-terminal domain and TACE transmembrane domain, respectively.…”
Section: Discussionmentioning
confidence: 76%
“…For immunoprecipitation, 200 g of total protein was incubated for 2 h at 4°C with 3 g of anti-TACE antibody (QED Biosciences, San Diego), anti-EGFR antibody (Upstate Biotechnology), or 2 g of anti-c-Src antibody (Santa Cruz Biotechnology) with gentle agitation, followed by protocols reported in ref. 15.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These kinases might be activated by cytokines or by structural alterations. For instance, EGFR over-expression and activation may underlie STAT activation in breast, lung and head and neck cancer (Zhang et al, 2004). Constitutive activation or dysregulated expression of STATs is detected in primary tumors and cancer cell lines, including leukemia, multiple myeloma, lymphomas, melanoma and cancers of the breast, skin, lung, ovaries, pancreas, prostate, kidney, thyroid, and head and neck (Desrivieres et al, 2006).…”
Section: Signal Transducer and Activator Of Transcription (Stat) 3/5mentioning
confidence: 99%